ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEJADIAN BBLR DI PUSKESMAS PERKOTAAN KABUPATEN BANJARNEGARA - Dewie Sulistyorini; Shinta Siswoyo (Universitas Muhammadiyah Semarang, 2014)
Targeting the Millennium Development Goals by 2015 is to reduce infant and childmortality rate by two-thirds from 1990 that is equal to 23 per 1,000 live births. InfantMortality Rate (IMR) in Central Java Province in 2012 was 10.75 per 1,000 live births, anincrease when compared with the year 2011 was 10.34 per 1,000 live births. LBW is a majorfactor in the increased mortality, morbidity and disability neonates, infants and children aswell as provide long-term impact on life in the future. LBW is a major cause of neonataldeath. Infant Mortality in Banjarnegara district contributes greatly to the IMR Central Java.Infant Mortality in Banjarnegara district in 2013 is 18.21 per 1,000 live births. That numberstill ranks highest in Central Java Province. The cause of death is still at about the low birthweight (LBW) and asphyxia, and more than 70% of deaths occur in the perinatal period is 0-7days old.This study using analytical survey is a study concerning how the risk factors studied withretrospective approach. Data collection techniques using secondary data obtained from the KIAbook and cohort at each health center. The tools used in the research is by using a checklist thatcontains the name of the subject, and some of the symptoms as well as other criteria of thetarget observation. Where the research is done in 3 Puksesmas Urban region has the highest number of LBW Banjarnegara District Health Office. The results of thestudy, factors affecting LBW include gemmeli (p=0,029) and anemia (p=0,188). Keywords: Risk Factors, LBW, Urban